2017
DOI: 10.1007/s00284-017-1427-3
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Species Diversity of Fungi in Rivers with Various Contaminations

Abstract: The main objective of this work was to determine the abundance and species diversity of fungi in the waters of selected rivers of Central Europe, NE Poland (Augustów Lakeland), differing in size, physical and chemical properties, and streamflow rate. The minimum abundance of fungi in the analysed rivers was recorded for a river with low concentration of organic matter (8200 CFU/mL, Czarna Hańcza River), and maximum for a strongly anthropogenically polluted river (24,800 CFU/mL, Kamienny Bród River). A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 33 publications
2
10
1
2
Order By: Relevance
“…KEGG analysis indicated that ZLH was highly associated with neurodegenerative disease and cancers, but it is still a primary water supply for the surrounding population. Certain pathogenic fungi are tolerant to alkaline conditions and are predominant in water [51]. We believe that the high pH values of QH, SHX, and ZLH indicate higher concentrations of pathogenic species and an increased risk for disease in humans and aquatic species.…”
Section: Discussionmentioning
confidence: 92%
“…KEGG analysis indicated that ZLH was highly associated with neurodegenerative disease and cancers, but it is still a primary water supply for the surrounding population. Certain pathogenic fungi are tolerant to alkaline conditions and are predominant in water [51]. We believe that the high pH values of QH, SHX, and ZLH indicate higher concentrations of pathogenic species and an increased risk for disease in humans and aquatic species.…”
Section: Discussionmentioning
confidence: 92%
“…As water quality variation is strongly related to anthropogenic activities (except spatiotemporal factors), many studies have focused on the impacts of such activities on fungal communities. Bergfur and Sundberg (2014) determined that agricultural land use can have significant effects on fungal communities and Pietryczuk et al (2018) reported that anthropogenically polluted rivers show higher taxonomic diversity of fungi. Overall, most studies on river ecosystems have demonstrated that anthropogenic activities (e.g., nutrient, micropollutant, and microplastic discharge) can shape fungal community composition (Kettner et al, 2017; Tlili et al, 2017; Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that this species is able to grow in waters rich in organic matter. The presence of Candida albicans is mainly observed in freshwater ecosystems, especially those with high levels of organic matter [ 22 , 30 , 31 ]. The observed increase in microfungal biomass exposed to humic acid may be associated with the specific structure of these compounds, abundant in aromatic compounds including phenols [ 32 ].…”
Section: Discussionmentioning
confidence: 99%